Impact of SIV infection on mycobacterial lipid-reactive T cell responses in Bacillus Calmette-Guérin (BCG) inoculated macaques - Walker, Edith M.; Merino, Kristen M.; Slisarenko, Nadia; Grasperge, Brooke F.; Mehra, Smriti; Roy, Chad J.; Kaushal, Deepak; Rout, Namita (Frontiers in Immunology, 2023)
Although BCG vaccine protects infants from tuberculosis (TB), it has limited efficacy in adults against pulmonary TB. Further, HIV coinfection significantly increases the risk of developing active TB. In the lack of defined correlates of protection in TB disease, it is essential to explore immune responses beyond conventional CD4 T cells to gain a better understanding of the mechanisms of TB immunity. Here, we evaluated unconventional lipid-reactive T cell responses in cynomolgus macaques following aerosol BCG inoculation and examined the impact of subsequent SIV infection on these responses. Immune responses to cellular lipids of M. bovis and M. tuberculosis were examined ex vivo in peripheral blood and bronchioalveolar lavage (BAL). Prior to BCG inoculation, innate-like IFN-γ responses to mycobacterial lipids were observed in T cells. Aerosol BCG exposure induced an early increase in frequencies of BAL T cells, a dominant subset of lipid-reactive T cells, along with enhanced IL-7R and CXCR3 expression. Further, BCG exposure stimulated greater IFN-γ responses to mycobacterial lipids in peripheral blood and BAL, suggesting the induction of systemic and local Th1-type response in lipid-reactive T cells. Subsequent SIV infection resulted in a significant loss of IL-7R expression on blood and BAL T cells. Additionally, IFN-γ responses of mycobacterial lipid-reactive T cells in BAL fluid were significantly lower in SIV-infected macaques, while perforin production was maintained through chronic SIV infection. Overall, these data suggest that despite SIV-induced decline in IL-7R expression and IFN-γ production by mycobacterial lipid-reactive T cells, their cytolytic potential is maintained. A deeper understanding of anti-mycobacterial lipid-reactive T cell functions may inform novel approaches to enhance TB control in individuals with or without HIV infection.